Progressive squamous epithelial neoplasia in K14-human papillomavirus type 16 transgenic mice. - Arbeit, J M (1994)
To model human papillomavirus-induced neoplastic progression, expression of the early region of human papillomavirus type 16 (HPV16) was targeted to the basal cells of the squamous epithelium in transgenic mice, using a human keratin 14 (K14) enhancer/promoter. Twenty-one transgenic founder mice were produced, and eight lines carrying either wild-type or mutant HPV16 early regions that did not express the E1 or E2 genes were established. As is characteristic of human cancers, the E6 and E7 genes remained intact in these mutants. The absence of E1 or E2 function did not influence the severity of the phenotype that eventually developed in the transgenic mice. Hyperplasia, papillomatosis, and dysplasia appeared at multiple epidermal and squamous mucosal sites, including ear and truncal skin, face, snout and eyelids, and anus. The ears were the most consistently affected site, with pathology being present in all lines with 100% penetrance. This phenotype also progressed through discernible stages. An initial mild hyperplasia was followed by hyperplasia, which further progressed to dysplasia and papillomatosis. During histopathological progression, there was an incremental increase in cellular DNA synthesis, determined by 5-bromo-2'-deoxyuridine incorporation, and a profound perturbation in keratinocyte terminal differentiation, as revealed by immunohistochemistry to K5, K14, and K10 and filaggrin. These K14-HPV16 transgenic mice present an opportunity to study the role of the HPV16 oncogenes in the neoplastic progression of squamous epithelium and provide a model with which to identify genetic and epigenetic factors necessary for carcinogenesis.